DisAssist: An internet of things and mobile communications platform for disabled parking space management - Lambrinos, Lambros; Dosis, Aristotelis (My University, 2013)
People with disabilities face many issues when it comes to parking in urban areas which include the limited availability of spaces allocated for their use and the unauthorised usage of such spaces. This paper presents DisAssist which is a system designed and developed based on the principles brought forward by the Internet of Things and Smart Cities initiatives; it integrates sensors and smart phones along with wireless and mobile communications to provide for better utilisation and management of parking spaces allocated for use by people with disabilities. Through the use of DisAssist, people with disabilities may obtain real-time availability of parking slots in an area of interest, reserve a slot and authenticate themselves when parking assisting the authorities with usage monitoring for law enforcement as well as capacity planning purposes. Entitlement verification is possible through a multitude of ways enabling users to embrace technology at the level and format they wish.
Keywords: Disabled parking space; Internet of Things; Parking monitoring; Parking reservation; Smart cities